The state of truth in the context of globalization - Nowak, Karolina (Ekonomia i Prawo. Economics and Law, 2020)
Motivation: This article addresses the issue of the functioning of modern societies in the context of worldview transformations related to globalization processes. Whether today’s globalization processes — the dissemination of specific models, designs, systems, tools and narrations in socio-cultural-economic-political dimensions — have significantly redefined the notion of truth and strengthened (or perhaps weakened) its validity (phenomenon)? The main motivation to undertake this research was the desire to show the role and the strengthening of value (truth) in social practice, in particular in relation to scientific and economic practice. Aim: The purpose of the article is to answer the question how globalization (in the socio-economic-cultural aspect) affects new ways of redefining the truth, treated as the axiological basis of scientific practice. The economic aspect has been taken into account in particular in the context of the establishment of a new (technological) approach to truth based on globalization processes taking place within the framework of network economics and on-demand economy. The literature review reconstructs two historically significant ways of redefining truth as the base value for scientific practice (autotelic and socio-useful) in order to show the breadth of socio-economic changes associated with the new definition of truth (as a technological value). The article is theoretical, based on philosophical considerations, recognized in a cultural perspective; the humanistic interpretation was applied. Results: The result of the research is to show: 1. the continuity of the process of redefining the truth, 2. the need to take into account the axiological context in relation to new types of economic practice.